A study of Predicting Consumption, Wine Involvement and Perceived Quality of Indian Red Wine - Patil, Sharad; Gupta Khan, Ashoo (International Journal of Psychosocial Rehabilitation, 2020)
Indian wine drinkers’ questionnaire responses measured consumption dimensions, product involvement, subjective knowledge, personality traits, and socio-demographics to predict red wine consumption and perceived quality. Total red wine consumed/week was predicted by wine involvement (product involvement), being male and self-monitoring (ability); the number of days/week drinking red wine was predicted by age and wine involvement (product sign) and higher income. Higher self-monitoring predicted buying more expensive wine. Wine involvement was predicted by wine subjective knowledge, reward responsiveness, need for cognition, and, negatively, by impulsivity (non-planning). Perceived quality was predicted by sensitivity to reward and older wine company and, negatively, by higher expenditure.